Autoimmune antibodies anti-AchR as biomarkers in Myasthenia Gravis - Antunes, Raquel Coelho Loyo Pequito (2015)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014